The synthesis of 2-epi-pumiliotoxin C via intramolecular alkene Cope-type hydroamination, and, New routes toward ketonitrones - Pfeiffer, Jennifer Y (University of Ottawa (Canada), 2010)
Despite recent advances in the field, the hydroamination methodology has not yet reached its full potential. This thesis focuses on new investigations in Cope-type hydroamination by first examining six-membered ring formation in order to explore and expand the scope of intramolecular Cope-type hydroamination of disubstituted olefins. This objective was achieved by synthesizing pumiliotoxin C (+/-)-3 and its epimer (+/-)-2 through the cyclization of a hydroxylamine precursor (+/-)-1 under transition metal-free reaction conditions.* In the second chapter we discuss the scarcity of methods to make ketonitrones 4 in the current literature and our approach to overcome this constraint using Cope-type hydroamination which involved heating allenes 5 and alkynes 6 with hydroxylamines under metal-free reaction conditions. Improved reaction conditions for the Schiff-base reactions of ketones will also be presented.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Organic.